Toxicogenomic Analysis Reveals Profibrogenic Effects of Trichloroethylene in Autoimmune-Mediated Cholangitis in Mice - Kopec, Anna K. (Toxicol Sci, 2014)
Epidemiological studies suggest that exposure to environmental chemicals increases the risk of developing autoimmune liver disease. However, the identity of specific chemical perpetrators and the mechanisms whereby environmental chemicals modify liver disease is unclear. Previous studies link exposure to trichloroethylene (TCE) with the development of autoimmune liver disease and exacerbation of autoimmunity in lupus-prone MRL mice. In this study, we utilized NOD.c3c4 mice, which spontaneously develop autoimmune cholangitis bearing resemblance to some features of primary biliary cirrhosis. Nine-week-old female NOD.c3c4 mice were given TCE (0.5 mg/ml) or its vehicle (1% Cremophor-EL) in drinking water for 4 weeks. TCE had little effect on clinical chemistry, biliary cyst formation, or hepatic CD3+ T-cell accumulation. Hepatic microarray profiling revealed a dramatic suppression of early growth response 1 (EGR1) mRNA in livers of TCE-treated mice, which was verified by qPCR and immunohistochemical staining. Consistent with a reported link between reduced EGR1 expression and liver fibrosis, TCE increased hepatic type I collagen (COL1A1) mRNA and protein levels in livers of NOD.c3c4 mice. In contrast, TCE did not increase COL1A1 expression in NOD.ShiLtJ mice, which do not develop autoimmune cholangitis. These results suggest that in the context of concurrent autoimmune liver disease with a genetic basis, modification of hepatic gene expression by TCE may increase profibrogenic signaling in the liver. Moreover, these studies suggest that NOD.c3c4 mice may be a novel model to study gene-environment interactions critical for the development of autoimmune liver disease.